The inferior frontal gyrus and cough - Homajoun Maslehaty (Clinics and Practice, 2014)
We present a case of a patient with a tumor close to the right inferior frontal gyrus. The only symptom this patient had was a disturbing dry cough. After removal of the tumor the cough disappeared immediately. Review of the literature showed that there is a control center of voluntary cough in the right inferior frontal gyrus. Our case suggests that there might be such a center, which can be affected by a tumor close to it.